Rescue alemtuzumab for refractory acute cellular rejection and bronchiolitis obliterans syndrome after lung transplantation. Issue 4 (22nd February 2017) - Ensor, Christopher R.; Rihtarchik, Lindsey C.; Morrell, Matthew R.; Hayanga, J. W. Awori; Lichvar, Alicia B.; Pilewski, Joseph M.; Wisniewski, Stephen; Johnson, Bruce A.; D'Cunha, Jonathan; Zeevi, Adriana; McDyer, John F.
Abstract: Refractory acute cellular rejection (rACR) is associated with death and bronchiolitis obliterans syndrome (BOS) post‐lung transplantation. We report the largest cohort of lung transplant recipients (LTRs) treated with rescue alemtuzumab for rACR or BOS. RACR outcomes included burden of ACR 30 days before and 180 days after rescue assessed by a novel composite rejection standardized score (CRSS, range 0‐6) and freedom from ≥A2 ACR. BOS outcomes included freedom from BOS progression and FEV1 decline >10%. Univariate parametric and nonparametric statistical approaches were used to assess treatment response. Kaplan‐Meier method with log rank conversion was used to assess freedom from events. Fifty‐seven alemtuzumab doses (ACR 40 and BOS 17) given to 51 patients were included. Median time to rescue was 722 (IQR 42‐1403) days. CRSS declined significantly (3 vs 0.67, P <0.001) after rescue. Freedom from ≥A2 was 62.5% in rACR. Freedom from BOS progression was 52.9% at 180 days in the BOS cohort. Freedom from FEV1 decline >10% was 70% in BOS grade 1 and 14.3% in advanced BOS grades 2‐3. Infections developed in 72.5% and 76.5% of rACR and BOS groups. Rescue alemtuzumab appears useful for rACR. Patients with BOS 1 may have transient benefit, and patients with advanced BOS seem not to respond to alemtuzumab.